Smart Building Rating System: A Comparative Analysis of National and International Rating Systems - Hamidah, Amanah; Berawi, Mohammed Ali; Sari, Mustika; Saroji, Gunawan (UI Scholars Hub, 2025)
Smart buildings have become a key part of the Fourth Industrial Revolution, driven by the need for efficient, sustainable, and adaptive built environments. Their importance is growing alongside Indonesia’s effort to develop smart cities. This study compares Indonesia’s national smart building certification system, established under Ministerial Regulation No. 10 of 2023, with two international systems: the European Union’s Smart Readiness Indicator (SRI) and the SmartScore certification. The analysis uses a literature review and comparative method to examine each system’s assessment criteria, scoring method, and certification tier. The findings show that Indonesia’s regulation includes six parameters, such as cybersecurity and operational management. SRI covers nine technical domains with emphasis on energy efficiency and occupant comfort. SmartScore focuses on user functionality and technological foundation. The comparison shows both overlap and variation in technical coverage, sustainability goals, and adaptability to climate and user needs. Although Indonesia’s system is comprehensive, it would benefit from closer alignment with international standards and stronger regulatory support to improve adoption and building performance. This study recommends more government incentives, better infrastructure, and stronger stakeholder education to support smart building development in Indonesia.